PRECISION MEDICINE IN BREAST RECONSTRUCTION: CLINICAL ADVANCES, REHABILITATION AND PATIENT EDUCATION PERSPECTIVES - Michalina Chodór; Maciej Kokoszka; Aleksandra Tomaszewska; Kinga Karczewska; Sonia Mojzyk; Aleksandra Mierniczek; Aleksandra Ćwirko-Godycka; Nikola Murawska; Natalia Dymel; Ryszard Feret (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Breast cancer represents the most frequently diagnosed malignancy among women globally, affecting approximately 2.12 million new cases annually according to the Global Burden of Disease 2021 analysis. While radical mastectomy remains the primary surgical treatment, it often results in significant chest wall defects and axillary distortion with profound negative impacts on body image, psychological well-being, and overall quality of life (QoL). Breast reconstruction has evolved into an integral component of modern oncological treatment, extending beyond aesthetic considerations to encompass comprehensive patient-reported outcomes and functional recovery. Contemporary healthcare increasingly embraces precision medicine principles, wherein breast reconstruction serves as a paradigmatic field requiring personalized treatment algorithms that balance oncological safety, aesthetic outcomes, and patient-specific variables. This comprehensive review synthesizes current evidence on precision medicine approaches in breast reconstruction, examining surgical innovations, postoperative rehabilitation strategies, and patient-centered outcome assessment.Materials and Methods: This review constitutes a thorough analysis of peer-reviewed literature obtained from the PubMed scientific database, synthesizing materials spanning from the Introduction through References of the manuscript. The analysis encompasses recent advances in surgical techniques, rehabilitation protocols, bioengineered technologies, and patient-reported outcome measures employed in breast reconstruction following mastectomy.Key Findings: Contemporary breast reconstruction integrates three interdependent pillars: advanced surgical techniques, targeted postoperative rehabilitation, and precise patient-centered outcome assessment via validated tools such as BREAST-Q. Modern surgical strategies include nipple-sparing mastectomy (NSM) with immediate reconstruction, prepectoral breast reconstruction utilizing acellular dermal matrices (ADM), and autologous free flap techniques (particularly DIEP flaps). Enhanced Recovery After Surgery (ERAS) protocols significantly reduce hospitalization duration to post-operative day 3 with equivalent complication rates compared to traditional protocols. Early mobilization and structured physical therapy demonstrably improve shoulder range of motion and functional outcomes. Patient-reported outcomes consistently demonstrate that autologous reconstruction produces superior satisfaction and health-related quality of life compared to implant-based approaches. Emerging tissue engineering technologies, including three-dimensional bioprinting, adipose-derived stem cells, and bioengineered scaffolds, represent promising future directions for functional breast reconstruction with reduced morbidity.Conclusions: Precision medicine in breast reconstruction requires integrated decision-making incorporating molecular data, clinical variables, and subjective patient experiences throughout all treatment phases. Optimal outcomes depend upon personalized surgical strategy selection, early and targeted rehabilitation, and standardized measurement of patient-reported outcomes. This multifaceted, precision-based approach ensures maximal functional and psychological benefits while minimizing procedural morbidity, ultimately delivering comprehensive quality of life improvements for breast cancer survivors.